Implementation of the Geometry Optical Material Module Based on a Scientific Approach - Desmarani, Suci; Audina, Diskha Ayu (Program Magister Teknologi Pendidikan Universitas Jambi, 2016)
Many students find it difficult to receive lessons because students do not have a handbook. Meanwhile, for schools that are still implementing the 2013 curriculum, textbooks that are in accordance with the scientific approach are not yet available. This research aims to provide solutions based on the problems faced by students, namely by developing teaching materials, namely modules. The research design is development (Research and Development). Meanwhile, the type of research is qualitative and quantitative research. Meanwhile, the development model is ADDIE. The technique used to collect data is by distributing questionnaires. The data analysis technique is a percentage technique, while the data type is quantitative data in the form of percentage values of student responses and qualitative data in the form of analysis results from the percentage of student responses. In this study, reliability was measured using the Kuder Richardson KR-20 formula. The physics module based on a scientific approach for high school class.